The relationship between internalizing problems and acute exercise duration in children with attention-deficit/hyperactivity disorder: The role of frontal alpha asymmetry. (November 2021) - Chueh, Ting-Yu; Hsieh, Shu-Shih; Tsai, Yu-Jung; Yu, Chien-Lin; Huang, Chung-Ju; Hung, Tsung-Min
Highlights: Lower frontal alpha asymmetry (characterized by relatively lower left-side frontal activity and greater right-side frontal activity) is associated with internalizing problems in children with attention-deficit/hyperactivity disorder, with both hemispheres contributing to this relationship. No relationship was found between internalizing problems and other alpha asymmetry indices. Fifty minutes of acute moderate-intensity aerobic exercise can increase frontal alpha asymmetry, predominately resulting from increased left-side frontal activity (lower alpha power), in children with attention-deficit/hyperactivity disorder. Abstract: Background: Frontal alpha asymmetry (FAA) has been associated with the regulation of certain types of internalizing psychopathologies, and is affected by acute aerobic exercise (AE). However, no previous studies have examined the association between FAA and internalizing problems or the effects of acute exercise on FAA in children with ADHD. Aims: This study had two objectives. First, it aimed to examine the relationship between FAA and internalizing behaviors in children with ADHD. Second, it sought to investigate the differential effects of acute AE (30 and 50 min) on FAA. Method: Participants were assigned to one of the following three groups: 50 min of AE, 30 min of AE, and a control group. Resting electroencephalogram (EEG) data were recorded before and after their respective treatments. EEG data from 43 participants were analyzed to investigate the association between pre-test FAA and internalizing problems as assessed by Child Behavior Checklist scores. Additionally, EEG data from 46 participants were analyzed to examine the effects of acute AE on post-test FAA while controlling for pre-test FAA. Results: Pre-test FAA was found to be significantly negatively associated with internalizing problems, with both hemispheres contributing to this association. Regarding the effects of acute exercise, the 50-minute AE group had highest post-test FAA, reflected by the increased relative left-side frontal activity. Conclusions: These findings suggest that FAA is a biological marker of internalizing symptoms in children with ADHD, and a 50-minute session of AE can effectively modulate FAA.